Mastering rational XDE - Boggs, Wendy (Sybex, 2003)
Rational XDE cures many of the headaches of application modeling and development by bringing the two processes closer together than ever before. Mastering Rational XDE shows you how to get maximum relief using this powerful tool, which lets you model within your preferred IDE, generate code automatically, and maintain tight synchronization between model and code at all times. One of the keys that unlocks this enormous power is the large example project that runs through Mastering Rational XDE, divided into a series of exercises that teach you to create use case and analysis models, move from analysis to design, create databases, publish and report models, and apply and create patterns. By working through this book, you'll be able to develop sophisticated, flexible object-oriented applications that are efficient to maintain and upgrade.